2011
DOI: 10.1186/1471-2407-11-139
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of the Axl and PDGFR-α by c-Met through a ras- and Src-independent mechanism in human bladder cancer

Abstract: BackgroundA cross-talk between different receptor tyrosine kinases (RTKs) plays an important role in the pathogenesis of human cancers.MethodsBoth NIH-Met5 and T24-Met3 cell lines harboring an inducible human c-Met gene were established. C-Met-related RTKs were screened by RTK microarray analysis. The cross-talk of RTKs was demonstrated by Western blotting and confirmed by small interfering RNA (siRNA) silencing, followed by elucidation of the underlying mechanism. The impact of this cross-talk on biological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 44 publications
4
60
0
Order By: Relevance
“…2A) revealing signaling cross-talk within the MPNSTs between MET and the PDGF and IL receptors (PDGF-R and ILR, respectively). This is in concordance with previous studies identifying crosstalk between receptor tyrosine kinases and MET in cancer cell lines (22,23). We show that HGF-induced wound healing in the ST8814, S1844.1, and S1507.2 cells was significantly reduced after inhibition of MET with both the SU11274 and PF-4217903 inhibitors (Fig.…”
Section: Resultssupporting
confidence: 93%
“…2A) revealing signaling cross-talk within the MPNSTs between MET and the PDGF and IL receptors (PDGF-R and ILR, respectively). This is in concordance with previous studies identifying crosstalk between receptor tyrosine kinases and MET in cancer cell lines (22,23). We show that HGF-induced wound healing in the ST8814, S1844.1, and S1507.2 cells was significantly reduced after inhibition of MET with both the SU11274 and PF-4217903 inhibitors (Fig.…”
Section: Resultssupporting
confidence: 93%
“…As Fra-1 controls tumour cell motility and proliferation and is widely expressed in cells of bladder tumours, molecular pathways upstream or downstream of Fra-1 represent attractive potential therapeutic targets. In a recent study, IHC analysis of AXL expression has been reported in T 2 -T 4 bladder cancer (n ¼ 65) (Yeh et al, 2011). Overexpression of AXL was detected in 80% of samples, which exactly coincides with the proportion of Fra-1-positive T 2 -T 4 tumours revealed in this study.…”
Section: Discussionsupporting
confidence: 88%
“…19,43 However association and transactivation of AXL with EGFR and cMet would limit the effects of targeted therapies. 44,45 To comprehend the efficiency of SKI606 and MPCD84111 on the migration of TNBC cells we examined the targets of SKI606 and MPCD84111. Based on our experiments we concluded that SKI606 has 40% more cellular targets than MPCD84111 but still both compounds commonly affect the migration related Src family kinases ( Table 1 and Fig 4).…”
Section: Discussionmentioning
confidence: 99%